2020
DOI: 10.3390/coatings10080793
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of AlCrN Coatings Deposited Using Cathodic Arc Evaporation

Abstract: Al–Cr–N coatings were formed at various nitrogen pressures, substrate bias voltages and substrate temperatures using cathodic arc evaporation. The relationship between technological parameters and properties of the coatings was investigated. The phase and chemical composition of the coatings, roughness, hardness, adhesion and thermal stability were analyzed by X-ray diffraction (XRD), scanning electron microscope (SEM), Energy-dispersive X-ray spectroscopy (EDX), micro-indenter, Rockwell, scratch tester and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 43 publications
6
36
1
Order By: Relevance
“…Furthermore, the toughness of the duplex-treated Vanadis 4 sample was even greater than the 1.2379 duplex's, with a CPR value of 2928 N 2 . These values indicate the great capacity of the coatings to resist crack propagation, and are higher than those reported in [53], which reported CPR values of approximately 1468 N 2 for NiCrN coatings deposited on M2 tool steel, and in [66], which showed CPR values of around 1900 N 2 for AlCrN coatings deposited on HS6-5-2 steel. However, similar results were reported in [61], with CPR values between 1500 and 4300 N 2 depending on the Ni content of the CrAlNiN coatings deposited onto AISI M2 high-speed tool steel substrates.…”
Section: Adhesion Testscontrasting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, the toughness of the duplex-treated Vanadis 4 sample was even greater than the 1.2379 duplex's, with a CPR value of 2928 N 2 . These values indicate the great capacity of the coatings to resist crack propagation, and are higher than those reported in [53], which reported CPR values of approximately 1468 N 2 for NiCrN coatings deposited on M2 tool steel, and in [66], which showed CPR values of around 1900 N 2 for AlCrN coatings deposited on HS6-5-2 steel. However, similar results were reported in [61], with CPR values between 1500 and 4300 N 2 depending on the Ni content of the CrAlNiN coatings deposited onto AISI M2 high-speed tool steel substrates.…”
Section: Adhesion Testscontrasting
confidence: 54%
“…The adhesion values obtained in this study are higher than those reported in other studies where conventional PVD techniques were used. References [65,66] reported Lc2 values of around 80-90 N for high-speed steel substrates coated by cathodic arc evaporation PVD (AlTiN and AlCrN, respectively), while [67] presented Lc2 values of 30 N for multilayer Ti/TiAlN/TiAlCN coatings deposited on tool steels by magnetron sputtering. Many other studies showed Lc2 values from 50 N to 80 N for duplex (nitriding + PVD) hard coatings deposited on tool steels [1,[68][69][70].…”
Section: Adhesion Testsmentioning
confidence: 99%
“…This is illustrated in Figure 17a-d. Further reported effects of deposition pressure include increased hardness and an influence on the phase structure [91,92]. The structure of arc-deposited AlCr-based coatings depends not only on the cathode composition, process temperature, substrate bias potential, arc current and reactive gas pressure, but also on the arc source design, in a manner that is similar to the case of AlTi-based coatings [9].…”
Section: Control Of Coating Morphology Stress and Texturementioning
confidence: 99%
“…Surface morphology, and in particular the density of macroparticles in arc deposition processes, can be influenced by the deposition pressure where fewer macroparticles are generated and smoother coatings are obtained at higher pressure [90][91][92], see also the example in Figure 17. This effect can be rationalised through a higher degree of poisoning on the target surface at an elevated pressure.…”
Section: Control Of Coating Morphology Stress and Texturementioning
confidence: 99%
“…Currently, the adhesion achieved by PVD coatings is very high, with LC3 critical load values of the order of 100 N [16][17][18][19]; in contrast, the adhesion of DLC coatings is not as high on soft substrates such as stainless steel.…”
Section: Introductionmentioning
confidence: 99%